RECONSTRUCTION OF TABARRU' FUND GOVERNANCE THROUGH QARD CONTRACT AT ASKRIDA SYARIAH INSURANCE - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Deni Mukti Hidayat; Adi Rosyadi; Teguh Supriyadi; Saiful Ali (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
Aim of this research is to analyze the role of the qard contract in sustaining the tabarru’ fund at Askrida Syariah Insurance. Utilizing a descriptive qualitative approach through literature review and operational practices of Islamic insurance, findings reveal that the reconstruction of the qard contract not only maintained underwriting discipline but also enhanced the resilience of tabarru' funds, improved governance quality, and reinforced the maqasid al-shariah orientation in contemporary Islamic insurance practices. Tabarru' funds face risks from underwriting deficits due to uncertainties in claims, participant dynamics, and investment yield volatility. The qard contract at Askrida Syariah Insurance acts as a liquidity buffer, maintaining claim payments while preserving the social function of the tabarru' fund. From a fiqh mu'amalah perspective, the qard is free from usury, gharar, and maisir, embodying the principles of ta'awun and distributive justice. Analysis of Islamic law objectives indicates that qard significantly contributes to wealth protection, fair risk distribution, and promoting the collective good. This research enriches sharia insurance literature by highlighting that the sustainability of tabarru' funds should not be evaluated only on contractual compliance but rather through the lens of maqasid-based governance.  Its practical contribution offers a conceptual framework for regulators, Islamic insurance firms, and Sharia Supervisory Boards to develop measurable, transparent, and long-term qard policies. This aims to mitigate moral hazard and bolster the Islamic insurance system's resilience. The study calls for enhanced governance guidelines regarding qard use in tabarru’ fund management, stressing the need for clearer regulatory standards, increased transparency, and improved risk management practices to ensure financial stability and sustainability in Islamic insurance operations.